IDENTIFIKASI AWAL KEMAMPUAN MEMBACA DASAR WARGA BINAAN DENGAN KESULITAN BELAJAR DI LEMBAGA PEMASYARAKATAN KELAS III RANGKASBITUNG - Puspita, Asni; Al-Anshori, Doddy Bakhtiar; Mulia, Dedi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Reading ability is a fundamental skill that plays an important role ini daily life, including for inmates in correctional institutions. This stufy aims to identify the basic reading abilities of inmates with learning difficulties at a Class III Correctional Institution in Rangkasbitung. This study employed a descriptive qualitative approach, with data collected through direct observation an simple communication. The research subjects consisted of three inmates with reading difficulties and one inmate with a hearing impairment. The result showed that the reading abilities of inmates varied, ranging from those who had not yet recognized letters to those who were able to read simple words but not complete sentences. The reading difficulties were associated with limitations in basic cognitive skills, working memory, and language processing. In addition, communication barriers experienced by the inmate with a hearing impairment affected the reading learning process. Based on these initial findings, inmates’ reading abilities need to be further identified through more structured assesments. Therefore, it is necessary to develop appropriate learning programs tailored to individual needs within the context of special education.